Efficacy in standard clinical practice of colonoscopic polypectomy in reducing colorectal cancer incidence. Issue 6 (1st June 2001) - Citarda, F; Tomaselli, G; Capocaccia, R; Barcherini, S; Crespi, M; Group, The Italian Multicentre Study
Abstract : BACKGROUND: Colorectal cancer is one of the leading causes of death from cancer in Western countries. Removal of adenomas is based on the assumption that it could lead to a reduction in the incidence of colorectal cancer, as demonstrated by the National Polyp Study in the USA. A critical issue is whether the benefit observed in clinical trials can also be observed in standard clinical practice. To address the issue, a multicentre Italian collaborative study was organised. METHODS: The study cohort comprised 1693 subjects of both sexes, aged 40–69 years, enrolled between 1980 and 1987 following a total colon examination (TCE) (that is, total colonoscopy or colonoscopy and double contrast barium enema), with removal of at least one adenoma larger than 5 mm in diameter. Exclusion criteria were genetic syndromes, previous adenomas or colorectal cancer, previous colonic resection, inflammatory bowel disease, or sessile adenomas more than 3 cm in diameter. Follow up ended in December 1996 by TCE or telephone interview, and review of the medical records, clinical files, or death certificates. Incidence ratios for colorectal cancer were compared with expected age and sex specific incidences in the Italian general population. RESULTS: Follow up data were obtained for 97.3% of cases for a total of 14 211 person/years. Mean follow up was 10.5 years. Six colorectal cancer cases (four in males, two in females) at various stages were ascertained (one at 29 months, two at five years, one at seven years, one at eight years, and one at 10 years from the index examination). The number of cancers expected in the reference population was 17.7 for an incidence ratio of 0.34 (confidence interval 0.23–0.63; p<0.01). CONCLUSIONS: Colonoscopic polypectomy substantially reduced the incidence of colorectal cancer in the cohort compared with that expected in the general population. These results are of particular relevance considering that those with adenomas are at increased risk of colorectal cancer and that this retrospective study was performed on data obtained in standard clinical practice. This observation strengthens the concept of effective population screening in view of the fact that adenomatous polyps are the most frequent neoplastic outcome of screening and their removal is associated with a decrease in the incidence of colorectal cancer.